Wet Cupping Therapy as A Complementary Intervention for Blood Glucose Reduction: Pre-Experimental Study - Mahfud, Mahfud; Sarwadhamana, R. Jaka; Muhammad, Dihan Fahry; Almubarok, Allama Zaki; Arroyan, Arroyan (Universitas Muhammadiyah Surakarta, 2026)
Diabetes mellitus is a metabolic disease characterized by persistently elevated blood glucose levels and is a significant global public health problem. Wet cupping therapy is a complementary therapy that supports glycemic control, although community-based evidence is still very limited. This study was conducted to examine the short-term impact of wet cupping therapy on blood glucose levels in adults. This study used a pre-experimental, single-group pre-test-post-test design and was conducted in Wirobrajan Village, Yogyakarta, Indonesia, in April 2025. Thirty adults aged 26-45 years who were not receiving glucose-lowering medication were recruited using quota sampling. Blood glucose levels were measured before and immediately after one wet cupping therapy session. A paired-sample t-test with a significance level of p < 0.05 was used to look at the data. The mean blood glucose level dropped from 131 mg/dL before the intervention to 117 mg/dL after, a difference of 14.2 mg/dL. This drop was statistically significant (p = 0.0001). These findings indicate that wet cupping therapy significantly reduces short-term blood glucose levels in adults. Wet cupping therapy can be considered a complementary intervention for glycemic control. However, further randomized controlled trials are needed to confirm these findings.